Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Siswa Tema 8 Kelas IV - Amna Mawilda; Arwin Arwin (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research to determine the effect of using the cooperative learning model with make a match type to students integrated learning outcomeTheme 8 Daerah Tempat Tingallku Class IV elementary school at Gugus VI Tanjung  Barulak sub district Batipuh Tanah DatarRegency. Research this manifold experiment with form Quasi Experimental Type Nonequivalent Control Group Design. Taking sample use technique cluster sampling. Instrument research that is test with technique data analysis using test precondition in the form of test normality, test homogeneity, and test-t. Based on t-test with α = 5% is obtained t-count is 3,09 and t-table is 2,02 with the t-test testing criteria that is if the value of t count > t table then H a is accepted. These results indicate that there is a significant effect of using the cooperative learning model type make a match on learning outcomes students Theme 8 Daerah Tempat Tingallku Class IV elementary school at Gugus VI Tanjung Barulak subdistrict Batipuh Tanah Datar Regency.Keywords : Cooperative Model, Make A Match, Results Learning, Learning Thematic, Learning Conventional.